Cold Mountain [videorecording (DVD)] - Minghella, Anthony; Law, Jude, 1972-; Kidman, Nicole, 1967-; Zellweger, Renée, 1969-; Frazier, Charles, 1950- (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
Inman, a young Confederate soldier, who is injured during the explosive 1864 battle of Petersburg, Virginia, is struggling to make his way home to Cold Mountain, NC, where his beloved Ada awaits him. In Inman's absence, Ada befriends Ruby, who helps her keep up her late father's farm. Meanwhile, in his travels, Inman encounters a menagerie of interesting and colorful characters.